The Double-track System of Terrorism Proscription in China - Zhang, Chi (Terrorism and political violence, 2021)
This paper contributes to the debate on terrorism designation and proscription by providing information and analysis on the “double-track” system of terrorism designation and proscription in China. It calls for greater attention to China’s terrorism proscription system as China has increased its engagement in international affairs and became more willing and capable of international cooperation in counterterrorism. The case of China provides important insights from a non-Western perspective into how states function in dealing with the challenge terrorism poses. In particular, it examines China’s efforts in balancing effective counterterrorism and the accountability of the government. Adopting an interpretivist approach based on primarily Chinese-language documents, it traces the development of China’s proscription regime since 2003 to illustrate its evolution from ad-hoc list-making to a more complicated system. Because of the difficulties in collecting information and presenting it as admissible evidence in court, like many other countries, China relies on the executive for terrorism designation and proscription. While the workings of China’s proscription system demonstrates authoritarian characteristics, the development of its proscription regime reveals how it sought to respond to the concerns about the legitimacy of its counterterrorism practice, for example, on issues of due process and presumption of innocence.